Tahrir al-ahkam fi tadbir ahl al-Islam - Ibn Jama'ah, Muhammad ibn Ibrahim; Shafi'i, Muhammad Hasan Muhammad Hasan Isma'il., editor; Mazidi, Ahmad Farid., editor (Bayrut : Dar al-Kutub al-Islamiyah, 2003)
PSZKLL